Commentary: It's time to talk about SUDEP. Issue 10 (16th October 2014) - Donner, Elizabeth; Buchhalter, Jeffrey
Summary Sudden unexpected death in epilepsy (SUDEP) is the most tragic potential outcome of epilepsy. Despite recommendations from epilepsy organizations in the United Kingdom and the United States, many neurologists choose not to discuss the risk of SUDEP with their patients with epilepsy. Yet, the literature clearly demonstrates that people with epilepsy and their caregivers want to know more about SUDEP. When health care providers do not provide information, people with epilepsy turn to other sources, risking misinformation and potentially increasing anxiety and distress. Sharing accurate information about SUDEP can optimize epilepsy self‐management and engage the person with epilepsy as a partner in their own care. Information about SUDEP must be part of the comprehensive education given to all people with epilepsy.